Anatomical standardization of small animal brain FDG-PET images using synthetic functional template: Experimental comparison with anatomical template - Coello, Christopher; Hjornevik, Trine; Courivaud, Frédéric; Willoch, Frode (Journal of neuroscience methods, 2011)
► Evaluation of absolute error when achieving spatial normalization of synthetic PET images to synthetic PET template compared to gold-standard ► Semi-automatic creation of PET-like images from MR images ► Improvement of PET spatial normalization using MR-derived functional template. Anatomical standardization (also called spatial normalization) of positron emission tomography (PET) small animal brain images is required to make statistical comparisons across individuals. Frequently, PET images are co-registered to an individual MR or CT image of the same subject in order to transform the functional images to an anatomical space. In the present work, we evaluate the normalization of synthetic PET (synPET) images to a synthetic PET template. To provide absolute error in terms of pixel misregistration, we created a synthetic PET image from the individual MR image through segmentation of the brain into gray and white matter which produced functional and anatomical images in the same space. When comparing spatial normalization of synPET images to a synPET template with the gold standard (MR images to an MR template), a mean translation error of 0.24 mm (±0.20) and a maximal mean rotational error of 0.85° (±0.91) were found. Significant decrease in misregistration error was measured when achieving spatial normalization of functional images to a functional template instead of an anatomical template. This accuracy strengthens the use of standardization methods where individual PET images are registered to a customized PET template in order to statistically assess physiological changes in rat brains.